The crucial influence of nano-copper (nano-Cu) on rumen function, ruminant productivity, and reproduction - Hudaya, Mohammad Firdaus; Sitaresmi, Pradita Iustitia; Ujilestari, Tri; Atmoko, Bayu Andri; Wulandari, Wulandari (Journal of Advanced Veterinary Research, 2025)
The requirements and factors that affect dietary requirements for various trace minerals and vitamins in ruminants remain poorly defined. Copper (Cu) is recognized for its pivotal role in the cellular osmotic balancing system, thereby contributing to numerous metabolic mechanisms in livestock. However, the provision is still often neglected to be given. Nanoparticle technology has emerged as promising approach to pursuit of optimizing the functionality and efficacy of feed mineral consumption. The objective of this article was to review the criteria and effects of supplementary feeding of nanomineral copper (nano-Cu) on rumen function, productivity and reproductive ability in ruminants. Additionally, the manufacturing process of nano-minerals was also briefly discussed that has not been widely published. The primary source of information reviewed for this article is published scientific literature.